Effect of Foliar Application of Zinc and Boron on the Growth and Yield of Wheat - Hossain, Md. Sajjad; Paul, Alok Kumar; Khan, Md. Asaduzzaman; Hasan, Mohammad Mahmudul (International Journal of Bio-resource and Stress Management, 2025)
The field experiment was conducted from November, 2022 to March, 2023 at the Sher-e-Bangla Agricultural University research farm in Dhaka, Bangladesh to evaluate the effect of foliar application of Zn and B on wheat. The experiment utilized a Randomized Complete Block Design with three replications, using BARI Gom-32 (wheat variety) as the test crop. Eight treatments were evaluated: T0=Control (No chemical fertilizers), T1=N140 P25 K110 S16 kg ha-1 (Recommended Fertilizer Dose), T2=T1+Zn and B application in soil @ Zinc 2 kg ha-1, B l kg ha-1, T3=T1+Zn and B once foliar application @ Zinc 2 kg ha-1, B 1 kg ha-1 at 50 DAS, T4=T1+Zn and B twice foliar application @Zinc 2 kg ha-1, B 1 kg ha-1 at 35 DAS and 50 DAS, T5=T1+Zn and B twice foliar application @ Zinc 1 kg ha-1, B 0.5 kg ha-1 at 35 DAS and 50 DAS, T6=T1+Zn and B once foliar application @ Zinc 1 kg ha-1, B 0.5 kg ha-1 at 35 DAS and T7=T1+Zn and B once foliar application @ Zinc 1 kg ha-1, B 0.5 kg ha-1 at 50 DAS. Results indicated that T4 significantly improved growth and yield attributes. Maximum plant height (79.46 cm), spike length (14.92 cm), flag leaf length (14.22 cm), total tillers plant-1 (5.33), spikelets spike-1 (15.86), grains spike-1 (45.53), 1000-seeds weight (56.00 g), grain yield (4.13 t ha-1), straw yield (4.74 t ha-1), and harvest index (46.52%) were recorded with T4. Conversely, the control (T0) showed the lowest results across all parameters.